A fire so wild ebook A novel. - Ruiz-Grossman, Sarah (2024)
Zibby Mag, Electric Literature, The Rumpus, and She Reads Most Anticipated Book of the Year "Grossman balances the social and political, the emotional and physical, with insight and precision. Her disparate characters all hail from different worlds, and it's a horrific thrill to witness their dramas unfurl and collide." — New York Times Book Review With the emotional echoes of Little Fires Everywhere and the lush atmosphere of Disappearing Earth, a riveting debut novel in which a wildfire creeps toward Berkeley, California, igniting tensions as characters from all walks of life confront the injustices lying beneath the city's surface. As a wildfire threatens Berkeley, the city's inhabitants are forced to reckon with the cracks in the lives they've built. Abigail, a wealthy homeowner, decides to throw a lavish birthday in a hillside mansion to raise money for the city's newest affordable housing project—and prove to her family that she's made something worthwhile of her life. Sunny, a construction worker who sleeps in a van along the bay's shore, is in the running for an apartment—but only if enough funds are raised at the party. As the heat and smoke from the approaching blaze descend upon the town, tensions rise and residents—young and old, haves and have nots—confront the inequities laid bare, and the fragility of building a life in a world on fire. Alternating among a colorful cast of characters, A Fire So Wild is a timely, tautly paced novel that questions why when everything burns, not everyone is left with scars.